A new serotype of calicivirus associated with an outbreak of gastroenteritis in a residential home for the elderly. Issue 8 (August 1981) - Cubitt, WD; Pead, PJ; Saeed, AA
Abstract : An outbreak of gastroenteritis involving residents and members of staff in a nursing home for the elderly is described. The agent associated with this episode was a calicivirus which is serologically distinct from two strains causing gastroenteritis in children. We believe that this is the first report of calicivirus infection in adults.